The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1007/s00221-017-5033-1
|View full text |Cite
|
Sign up to set email alerts
|

The Shepard–Risset glissando: music that moves you

Abstract: Sounds are thought to contribute to the perceptions of self-motion, often via higher-level, cognitive mechanisms. This study examined whether illusory self-motion (i.e. vection) could be induced by auditory metaphorical motion stimulation (without providing any spatialized or low-level sensory information consistent with self-motion). Five different types of auditory stimuli were presented in mono to our 20 blindfolded, stationary participants (via a loud speaker array): (1) an ascending Shepard-Risset glissan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Although the authors found a positive effect of multisensory stimulation on the subjective measures, postural steadiness was not affected by any form of stimulation. Conversely, Mursic et al (2017) investigated whether vection could be elicited through auditory stimulation that simulated metaphorical motion. Participants performed a Romberg test whilst standing on a pressure plate that recorded their CoP after which they viewed a series of visual stimuli aimed to elicit vection.…”
Section: Measures Of Vection and Participants' Task Instructionsmentioning
confidence: 99%
“…Although the authors found a positive effect of multisensory stimulation on the subjective measures, postural steadiness was not affected by any form of stimulation. Conversely, Mursic et al (2017) investigated whether vection could be elicited through auditory stimulation that simulated metaphorical motion. Participants performed a Romberg test whilst standing on a pressure plate that recorded their CoP after which they viewed a series of visual stimuli aimed to elicit vection.…”
Section: Measures Of Vection and Participants' Task Instructionsmentioning
confidence: 99%
“… 2 Auditory (e.g., Keshavarz et al., 2014 ; Mursic, Riecke, Apthorp, & Palmisano, 2017 ; Väljamäe, 2009 ) and tactile (e.g., Murata et al., 2014 ; Nordahl, Nilsson, Turchet, & Serafin, 2012 ) motion stimulation have both been reported to produce similar (although often less compelling) illusions of self-motion in blindfolded observers. Illusory self-motion can also be induced by passively rotating the limbs of blindfolded observers (e.g., Howard, Zacher, & Allison, 1998 ) or having them step on a treadmill (e.g., Bles, 1981 ).…”
mentioning
confidence: 99%
“…A depiction of the visual content of the abstract and naturalistic conditions can be found in Figure 3 A and B, respectively. The abstract auditory stimulus was an ascending Shepard-Risset glissando which has been shown to elicit vection [38], [39]. The naturalistic auditory stimulus was the sound of a train departing.…”
Section: Designmentioning
confidence: 99%